DEVELOPMENT AND VALIDATION OF AN ALGEBRA LITERACY TEST INTEGRATED WITH CHARACTER EDUCATION FOR ASSESSING MATHEMATICAL REASONING ABILITIES - Nursalam, Nursalam; Baharuddin; Amin, Badaruddin (MATEMATIKA DAN PEMBELAJARAN, 2025)
Mathematical reasoning has been recognized as one of the important skills in mathematics learning. The assessment of this cognitive skill necessitates a robust and well-structured evaluation instrument to ensure accurate measurement. This study aims to develop an algebra literacy assessment instrument integrated with character education reinforcement to evaluate students’ mathematical reasoning abilities. Adopting a design-based research approach through the Formative Research model (Tessmer), this study involves undergraduate students enrolled in the Mathematics Education Program at Universitas Islam Negeri (UIN) Alauddin Makassar. The research instruments include the algebra literacy assessment, validation sheets, and student response questionnaires. Data analysis is conducted to determine the validity, reliability, item difficulty level, discriminatory power, and practicality of the test items. The research and development process culminated in a validated 30-item algebra literacy assessment instrument integrated with character education reinforcement, demonstrating robust psychometric properties. The findings indicate that the developed instrument is a valid and reliable tool for assessing mathematical reasoning skills in higher education contexts.